The effect of adolescents’ perceived social support types on sense of meaning in life: the mediating role of social- emotional competence - Zhang, Chanjuan; Wang, Qiuying; Zhao, Wenyin; Yu, Haibo; Ma, Chao (Frontiers in Psychology, 2025)
BackgroundLacking a sense of meaning in life has been linked to negative emotions, anxiety, depression, suicidal ideation and suicide, and antisocial behavior. While perceived social support influences the sense of meaning in life, existing research has not precisely categorized perceived social support, with limited research on how a sense of meaning in life is expressed. This study aimed to examine how different types of perceived social support affect adolescents’ sense of meaning in life and the mediating role of social-emotional competence.MethodsUsing the Multidimensional Scale of Perceived Social Support, the Delaware Social and Emotional Competency Scale, and the Sense of Meaning in Life Scale, data were collected from 1,145 students from four middle schools in Province H, China. Latent profile analysis using Mplus 8.0 identified differences in social-emotional competence and sense of meaning in life across different perceived social support types. The mediating role of social-emotional competence between adolescents’ perceived social support types and sense of meaning in life was also examined.ResultsA follow-up analysis of the 1,145 data collected showed that: (1) Four potential categories of adolescent perceived social support existed: Poor (6.03%), Rich (25. 15%), Peer-oriented type (7. 16%), and Moderate (61.66%). Adolescents in these categories differed significantly in their social-emotional competence and sense of meaning in life, with both of the latter being stronger among adolescents in the Rich category than those in the Poor category. Taking the Poor type as the reference group, social-emotional competence mediated the relationship between the other groups and the sense of meaning in life.ConclusionThere is variation in adolescents’ perceived social support and social-emotional competence, which should be considered when designing interventions to enhance the sense of meaning in life. Educational practice should focus on enhancing adolescents’ social-emotional competence and the sense of meaning in life. Additionally, peer support groups should be nurtured, taking into account the core influence of peers on adolescents’ development, encouraging cooperation, interaction, and social interaction.